PENGARUH ISLAM DALAM SEJARAH PENGGUBALAN UNDANG-UNDANG TUBUH KERAJAAN JOHOR 1895 - Che Pa, Bharudin (Journal of Al-Tamaddun, 2007)
This article explains the history of the promulgation of The Constitution of The State of Johore 1895 and how Islamic elements have influenced the Constitution. The are some evidences that show how the contents of the Constitution have been influenced by Islamic religious texts from Riau Sumatera. This article will elaborate based on some parts of the text of the said Constitution which are congruent with Islamic principles. Among the aspects which shall be spelt out in detail include some of the legal provisions regarding the Johor State Executive Council, the criteria for the appointment of the Sultan of Johor, the appointment of cabinet ministers, leaders in general etc.